2015
DOI: 10.1103/physrevstper.11.010103
|View full text |Cite
|
Sign up to set email alerts
|

Narrated animated solution videos in a mastery setting

Abstract: Narrated animated solution videos were implemented in a clinical study that compared a mastery setting that employed repeated cycles of testing with instructional support to a group that had a single opportunity to experience the materials. The mastery setting students attempted sequential questions sets on a topic, with animated solutions between each set, until mastery was achieved, combining formative assessment with worked examples. Students showed significant improvement from their first to second tries o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Refs. [14,15]). Such practice could increase the fluency and retention of these skills and help students to solve more complex problems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [14,15]). Such practice could increase the fluency and retention of these skills and help students to solve more complex problems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Given the relatively simple nature of these procedural skills, it is possible that only brief, targeted instruction is needed for significant improvements in proficiency (e.g., see Refs. [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…These results are helpful not only in the specific domain of the STEM essential skill of vector math, but also in providing evidence and arguments for a more general framework to guide the design of computer-based training with simple feedback in similar domains. Note that while this study investigates factors effecting learning of a simple and essential procedure skill for physics, there have been other relatively recent lab studies in the physics education domain for improving student knowledge of specific topics [39,40] and conceptual reasoning in problem solving [41] that also show promise for application in a course.…”
Section: Summary and General Discussionmentioning
confidence: 99%
“…Recently, Schroeder et al [9] and Gladdening et al [10] have implemented something more similar to our work and focus, namely, computer-based mastery practice of specific skills in an education research lab setting and have shown it to be effective. The target skills in their studies tended to be specific to a particular physics problem type and subtopic (e.g., electric fields and potential for plane and spherical symmetries) and the studies focused on accuracy, while our target skills tend to be more broadly applicable (though not limited to this) and, as we will discuss below, we are aiming at accuracy, fluency, and retention.…”
Section: Introductionmentioning
confidence: 94%